Autoimmunity and Inflammation in X-linked Agammaglobulinemia - Hernandez-Trujillo, Vivian P. (2014)
PURPOSE: In the past, XLA was described as associated with several inflammatory conditions, but with adequate immune globulin treatment, these are presumed to have diminished. The actual prevalence is not known. METHODS: A web-based patient survey was conducted December 2011- February 2012. Respondents were recruited from the Immune Deficiency Foundation (IDF) patient database, online patient discussion forums and physician recruitment of patients. The questionnaire was developed jointly by IDF and by members of the USIDNET-XLA Disease Specific Working Group. Information regarding inflammatory conditions in patients with XLA was also obtained from the United States Immune Deficiency Network (USIDNET) Registry. RESULTS: Based on 128 unique patient survey responses, the majority of respondents (69 %) reported having at least one inflammatory symptom, with 53 % reporting multiple symptoms. However, only 28 % had actually been formally diagnosed with an inflammatory condition. Although 20 % reported painful joints and 11 % reported swelling of the joints, only 7 % were given a diagnosis of arthritis. Similarly, 21 % reported symptoms of chronic diarrhea and 17 % reported abdominal pain, however only 4 % had been diagnosed with Crohn’s disease. Data from the USIDNET Registry on 149 patients with XLA, revealed that 12 % had pain, swelling or arthralgias, while 18 % had been diagnosed with arthritis. Similarly, 7 % of these patients had abdominal pain and 9 % chronic diarrhea. CONCLUSIONS: Although patients with XLA are generally considered to have a low risk of autoimmune or inflammatory disease compared to other PIDD cohorts, data from this patient survey and a national registry indicate that a significant proportion of patients with XLA have symptoms that are consistent with a diagnosis of arthritis, inflammatory bowel disease or other inflammatory condition. Documented diagnoses of inflammatory diseases were less common but still increased over the general population. Additional data is required to begin implementation of careful monitoring of patients with XLA for these conditions. Early diagnosis and proper treatment may optimize clinical outcomes for these patients.